Prevalence of household food insecurity in the marginal area of Birjand, Iran - Moodi, Mitra; Salehiniya, Hamid; Mohtashaminia, Somayeh; Amininasab, Zahra; Arab-Zozani, Morteza (Frontiers in Sustainable Food Systems, 2023)
Introduction The right to food is a human right. Food insecurity refers to the inability to prepare proper and healthy food. Food insecurity is associated with adverse outcomes among households. To determine the prevalence of food insecurity, its level, and the factors affecting it among households covered by health centers in marginalized areas of Birjand city. Methods This descriptive-analytical cross-sectional study was performed on 396 households aged 20-60 years covered by health centers in the marginal areas of Birjand in 2019. We used a 9-item Household Food Insecurity Access Scale (HFIAS) questionnaire. Chi-square, Fisher, and logistic regression analyses were performed using SPSS 22 software at a significance level of less than 0.05. Results The mean age of the subjects was 34.04 ± 9.41 years. In total, 48% of the subjects had a level of food insecurity, of which 7.6% had severe, 12.6% moderate, and 27.5% mild insecurity. The prevalence of food insecurity in families with low members and higher levels of education is significantly lower (p < 001). Backward Logistic regression showed that illiteracy (OR: 8.26) and primary education (OR: 2.65), rental housing status (OR: 1.69), lower-income levels being covered by support organizations (OR: 3.13), employed members between 3-4 and more than five (OR: 2.73 and 2.93, respectively), and low weight (OR: 2.55) were associated with food insecurity. The prevalence of food insecurity in this study was high. Conclusion The high prevalence of insecurity in studied households is an alarm for the authorities, which can be due to poverty and the low level of nutritional literacy of households' heads and mothers. Helping to improve the quality of life of families and food insecurity of households by improving physical and economic access, increasing literacy and nutritional culture, and reducing the burden of non-communicable diseases related to nutrition is a suggested solution.